2019
DOI: 10.4049/immunohorizons.1800075
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating STAT4 and STAT5 Signaling Inhibitory Functions of SOCS3: Effects on CD8 T Cell Responses

Abstract: Cytokines are critical for guiding the differentiation of T lymphocytes to perform specialized tasks in the immune response. Developing strategies to manipulate cytokine-signaling pathways holds promise to program T cell differentiation toward the most therapeutically useful direction. Suppressor of cytokine signaling (SOCS) proteins are attractive targets, as they effectively inhibit undesirable cytokine signaling. However, these proteins target multiple signaling pathways, some of which we may need to remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Tong et al (2018) showed that Foxp3 cre Mettl3 fl/fl mice develop severe AID and increased inflammatory T H 1 and T H 17 responses. The Socs gene family is upregulated in Mettl3 ‐silenced T reg cells, and the SOCS proteins are capable of inhibiting the IL‐2‐STAT5 pathway, which is critical for T reg cell function (Betts et al, 2017; Hwang et al, 2019; C. Li & Park, 2020).…”
Section: M6a Methylation Modulates Adaptive Immune Cell Functionmentioning
confidence: 99%
“…Tong et al (2018) showed that Foxp3 cre Mettl3 fl/fl mice develop severe AID and increased inflammatory T H 1 and T H 17 responses. The Socs gene family is upregulated in Mettl3 ‐silenced T reg cells, and the SOCS proteins are capable of inhibiting the IL‐2‐STAT5 pathway, which is critical for T reg cell function (Betts et al, 2017; Hwang et al, 2019; C. Li & Park, 2020).…”
Section: M6a Methylation Modulates Adaptive Immune Cell Functionmentioning
confidence: 99%